Magnesium, Aging, and the Elderly Patient - Mladen Davidovic; Dejan Trailov; Dragoslav Milosevic; Branimir Radosavljevic; Pavle Milanovic; Snezana Djurica; Helena Loncar-Stevanovic; Radmila Stevic (The Scientific World Journal)
Magnesium, beyond any doubt, plays an important role in metabolism. Alterations of magnesium levels have an impact on many organs and systems, especially during aging. We had 156 participants aged 60–93 years (average 74.7 years) in our survey. Of them, 49 were men and 107 were women. Treatment with loop diuretics (Furosemid and Bumetanide) and magnesium levels was correlated, as well as the influence of magnesium levels on life span. Serum magnesium levels were measured in patients receiving diuretics and in the control group. Also, magnesium levels were measured in patients who passed away in the course of their disease and were compared with the control group. Magnesium levels in the diuretic group (100 patients) were 0.93 ± 0.094 mmol/l, while the average levels in the control group of 56 patients were 0.89 ± 0.075 mmol/l. In 29 patients who passed away, average magnesium levels were 0.92 ± 0.078 mmol/l, while in the control group (127 patients), magnesium levels were 0.93 ± 0.083 mmol/l. The differences were not statistically significant. There were no differences in serum magnesium of the elderly persons investigated regarding age group, gender, or type of diuretics. If methods of determining ionizing magnesium in serum or intracellular magnesium are not available, normal magnesium values in the serum are to be taken with a qualified acceptance.